2017
DOI: 10.1038/s41598-017-03505-2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the developmental and adult social environments mediate group dynamics and offspring traits in Drosophila melanogaster

Abstract: Developmental conditions can strongly influence adult phenotypes and social interactions, which in turn affect key evolutionary processes such as sexual selection and sexual conflict. While the implications of social interactions in phenotypically mixed populations at the individual level are increasingly well known, how these effects influence the fate of groups remains poorly understood, which limits our understanding of the broader ecological implications. To address this problem we manipulated adult phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 73 publications
6
54
0
Order By: Relevance
“…Further studies are nonetheless needed to provide a better understanding of the relationship between fitness and lipid storage in tephritid fruit flies. Our results also showed that, in general, high larval density had a negative effect on pupal and adult weights, which are in agreement with our predictions 1 and 2 as well as previous studies of diverse insect taxa (Bauerfeind & Fischer, 2005;Blanckenhorn, 1998;Lyimo, Takken, & Koella, 1992;Morimoto et al, 2016;Morimoto, Ponton, Tychsen, Cassar, & Wigby, 2017;Wertheim et al, 2002). This confirms our hypothesis that high larval density is costly for individuals (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…Further studies are nonetheless needed to provide a better understanding of the relationship between fitness and lipid storage in tephritid fruit flies. Our results also showed that, in general, high larval density had a negative effect on pupal and adult weights, which are in agreement with our predictions 1 and 2 as well as previous studies of diverse insect taxa (Bauerfeind & Fischer, 2005;Blanckenhorn, 1998;Lyimo, Takken, & Koella, 1992;Morimoto et al, 2016;Morimoto, Ponton, Tychsen, Cassar, & Wigby, 2017;Wertheim et al, 2002). This confirms our hypothesis that high larval density is costly for individuals (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…In invertebrates, including tephritid fruit flies, high-densities at the larval stage can decrease nutrient availability, and reduce adult body mass, reproductive success, and survival [e.g. 1 , 3 9 , 60 ], which can lead to a density-dependent effects on fitness that extends through generations 6 . However, high densities can also mitigate the negative effects of environmental stresses, and act as a buffering factor for individual fitness and survival [reviewed by 77 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 10 ]. Adult body size tends to correlate positively with female fecundity as well as male mating performance and reproductive success 5 , 11 ; accordingly, larval foraging behaviour is under productivity selection in females and sexual selection in males 11 15 , with profound effects on behavioural and evolutionary processes such as cognitive task performance, survival, reproduction, and ultimately sexual selection and sexual conflict 6 , 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…aegypti and A. gambiae; (Agnew et al 2002;Couret et al 2014;Gimnig et al 2002;Muriu et al 2013)]. In addition, high larval density also decreases larval and adult body mass and reproductive success [flies: D. melanogaster and B. tryoni (Diamantidis et al 2019;Morimoto et al 2016Morimoto et al , 2017aMorimoto et al , 2019a; mosquitoes: Ae. aegypti, Ae.…”
Section: Immediate and Delayed Density-dependent Effectsmentioning
confidence: 99%
“…First, we provide a functional definition of density aimed to standardise the terminology used in density-dependent studies-for our own reference while writing the review and also for future studies, where a functional definition of density will allow for comparative analysis across taxa. Next, we identify the biological levels at which density-dependent effects are manifested in non-social holometabolous insects and review the empirical evidences underpinning density-dependent effects on the larvae (density-dependent immediate effects), adults (density-dependent delayed effects), as well as populations (densitydependent ecological effects) and across generations (density-dependent evolutionary effects) (Agnew et al 2000;Bhavanam and Trewick 2017;Couret et al 2014;Creland et al 1986;Gimnig et al 2002;Hawley 1985;Morimoto et al 2019a;Morimoto et al 2017a). We then discuss recent evidences that density-dependent effects could affect the interactions between the host and its microbial community (density-dependent microbial interactions) and conclude by proposing a conceptual model to explain how density-dependent host-microbial interactions can modulate the strength of density-dependent effects across biological levels.…”
Section: Introductionmentioning
confidence: 99%